2018
DOI: 10.1002/ptr.6240
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroxy stilbene glucoside protected against diabetes‐induced osteoporosis in mice with streptozotocin‐induced hyperglycemia

Abstract: Tetrahydroxy stilbene glucoside (TSG), an active component from medicinal herb Polygonum multiflorum Thunb, could block the activity of the tissue reninangiotensin system (RAS), which plays a critical role in development of diabetic osteoporosis. This study aimed to determine if TSG therapy could alleviate bone deteriorations in diabetic mouse model induced by streptozotocin. The diabetic mice showed the loss of trabecular bone mass and the changes of trabecular bone microarchitectural parameters as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Reducing osteoclast differentiation-associated pathways by HSW may therefore represent a potential method for therapeutic intervention to prevent diabetes-related bone loss. In contrast, a previous study showed that THSG increases osteoblastogenic genes such as runt-related transcription factor 2 ( RUNX-2 ), OCN , and ALP in STZ-induced diabetic mice (Zhang et al, 2019). Our data did not show significant changes in RUNX-2 , OCN , and ALP between groups (data not shown).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Reducing osteoclast differentiation-associated pathways by HSW may therefore represent a potential method for therapeutic intervention to prevent diabetes-related bone loss. In contrast, a previous study showed that THSG increases osteoblastogenic genes such as runt-related transcription factor 2 ( RUNX-2 ), OCN , and ALP in STZ-induced diabetic mice (Zhang et al, 2019). Our data did not show significant changes in RUNX-2 , OCN , and ALP between groups (data not shown).…”
Section: Resultsmentioning
confidence: 71%
“…Hwang et al (2016) and Kim et al (2018b) reported that Heshouwu hot water extract and tetrahydroxystilbene glucoside (THSG), which is a bioactive compound of Heshouwu, prevent bone loss in estrogen deficient mice. Zhang et al (2019) recently reported that THSG protects against diabetes-induced osteoporosis in mice with streptozotocin (STZ)-induced diabetes. However, it remains unknown if Heshouwu can regulate diabetes-induced bone loss in vivo , or the mechanism by which its effects occur.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism involved in molecular binding and biological cascade response between tanshinone IIA and renin protein need to be further identified. Previous studies have demonstrated that some natural products like salidroside and tetrahydroxy stilbene glucoside (Zhang et al 2019) could affect tissue ANG II level, while this study is the first to explore and report that the naturally occurring product tanshinone IIA from SMB could target renin activity, which, at least partially, explained that SMB could reduce ANG II-stimulated collagen synthesis in cardiac fibroblasts (Ling et al 2009).…”
Section: Discussionmentioning
confidence: 68%
“…Since high renin activity and enhanced ANG II expression contributed to the development of bone deteriorations associated with hyperglycaemia Zhang et al 2019), the beneficial effects of tanshinone IIA on bone tissue was evaluated in diabetic mice. Treatment of diabetic mice with tanshinone IIA markedly increased trabecular BMD and improved trabecular bone micro-architecture as well as enhanced trabecular bone area, in accordance with that tanshinone IIA exerted bone-sparing function in ovariectomized mice (Cheng et al 2018) and rats (Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tetrahydroxy stilbene glucoside (TSG), which is an active component of P. multiflorum, was found to be effective in HFD-induced CF-1 diabetic mice [15]. Subsequent research indicated that TSG could inhibit of the tissue renin-angiotensin system (RAS), which plays a critical role in development of diabetic osteoporosis [16].…”
Section: Introductionmentioning
confidence: 99%